Exploring the influence of Chinese online patient trust on telemedicine behavior: insights into perceived risk and behavior intention - Liu, Chang; Wang, Jiaqi; Chen, Ran; Zhou, Wusi (Frontiers in Public Health, 2024)
As a supplement to medical services, telemedicine is of great significance to alleviate the shortage of health resources in China. Based on the traditional consumer behavior measurement model the Technology Acceptance Mode/Theory of Planned Behavior (TAM/TPB), this paper divides online patient trust into six dimensions: perceived risk, personal trust tendency, doctors’ credibility, hospitals’ credibility, websites’ credibility, and system guarantee. On this basis, a structural equation model (SEM) was used to explore the influence of each dimension of online patient trust on online patient intention, behavior choice, and pre-factors. A total of 582 valid questionnaires were distributed to selected patients with experience in using mobile healthcare services in the vicinity of hospitals and communities, as well as to users who shared their experiences in the discussion forums of mobile healthcare websites. The results show that online patient trust has a significant positive impact on telemedicine behavior intention selection, with a standardized path coefficient being as high as 0.866. Doctors’ credibility, system guarantee, and website credibility have significant positive effects on online patient trust, with standardized path coefficients of 0.401, 0.260, and 0.226, respectively. Hospital trustworthiness and personal trust propensity have no significant effect on online patient trust. Perceived risk has a significant negative effect on online patient trust, with a standardized path coefficient of −0.118. The research findings suggest that health departments and mobile healthcare providers can enhance mobile healthcare services by considering the patients’ perspectives, elevate their online trust levels, and foster a deeper understanding, safety consciousness, and confidence in telehealth services. On this basis, it can be concluded that only the participation of government, medical subjects, and online patients can effectively reduce perceived risks, improve perceived characteristics of online patients, enhance online patient trust, and promote the real willingness and behavior choice for online medical services, effectively improving the positive role of telemedicine in increasing health benefits to people.